Basement Membrane Defects in Genetic Kidney Diseases - Chew, Christine; Lennon, Rachel (Frontiers in Pediatrics, 2018)
The glomerular basement membrane (GBM) is a specialised structure with a significant role in maintaining the glomerular filtration barrier. This GBM is formed from the fusion of two basement membranes during development and its function in the filtration barrier is achieved by key extracellular matrix (ECM) components including type IV collagen, laminins, nidogens and heparan sulfate proteoglycans (HSPGs). The characteristics of specific matrix isoforms such as laminin-521 (α5β2γ1) and the α3α4α5 chain of type IV collagen are essential for the formation of a mature GBM and the restricted tissue distribution of these isoforms makes the GBM a unique structure. Detailed investigation of the GBM has been driven by the identification of inherited abnormalities in matrix proteins and the need to understand pathogenic mechanisms causing severe glomerular disease. A well-described hereditary GBM disease is Alport syndrome, associated with a progressive glomerular disease, hearing loss and lens defects due to mutations in the genes COL4A3, COL4A4 or COL4A5. Other proteins associated with inherited diseases of the GBM include laminin β2 in Pierson syndrome and LMX1B in Nail Patella syndrome. The knowledge of these genetic mutations associated with GBM defects has enhanced our understanding of cell-matrix signalling pathways affected in glomerular disease. This review will address current knowledge of GBM-associated abnormalities and related signalling pathways, as well as discussing the advances towards disease-targeted therapies for patients with glomerular disease.